Hubungan antara Umur dan Status Gizi dengan Kelelahan Kerja pada Pekerja Lapangan PT Pelabuhan Indonesia IV (Persero) Cabang Bitung - Amin, Marsela D.; Kawatu, Paul A. T.; Amisi, Marsella D. (e-Biomedik, 2019)
Abstract: Work-related fatigue results in decrease of concentration during working. Factors that cause work-related fatigue are inter alia heavy-work activities, work and mental burdens, unergonomic workplaces or tools, lack of concentration resulting in mistakes, work-related stress, work-related illnesses, injuries, and workplace accidents. Field workers at PT Pelabuhan Indonesia IV (Persero) Cabang Bitung has a variety of works as well as nutritional status. This study was aimed to determine the relationship between age and nutritional status with work-related fatigue among field workers at PT Pelabuhan Indonesia IV (Persero) Cabang Bitung. This was an observational analytical study with a cross-sectional design. We used purposive sampling and obtained 50 workers as respondents. Data were analyzed by using the Spearman rank test. The results showed that the correlation between age and work-related fatigue obtained a p-value of 0.000 and an r-value of 0.683. Furthermore, the correlation between nutritional status and work-related fatigue obtained a p-value of 0.003 and an r-value of -0.418. In conclusion, there was a strong-positive relationship between age and work-related fatique; and a moderate-negative relationship between nutritional status and work-related fatique among field workers at PT Pelabuhan Indonesia IV (Persero) Cabang Bitung.Keywords: work-related fatigue, age, nutritional statusÂ Abstrak: Kelelahan kerja berdampak pada penurunan konsentrasi saat bekerja. Faktor penyebab terjadinya kelelahan akibat kerja antara lain aktivitas berat, beban kerja dan mental, tempat kerja atau alat yang tidak ergonomis, kurang konsentrasi yang dapat berdampak terjadinya kesalahan, stres akibat kerja, penyakit akibat kerja, cedera, dan kecelakaan kerja. Pekerja lapangan di PT Pelabuhan Indonesia IV (Persero) Cabang Bitung memiliki jenis pekerjaan yang berbeda-beda dan memiliki status gizi yang beragam. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara umur dan status gizi dengan kelelahan kerja pada pekerja lapangan di PT Pelabuhan Indonesia IV (Persero) Cabang Bitung. Jenis penelitian ialah analitik observasional dengan desain potong lintang. Teknik pengambilan sampel menggunakan purposive sampling sebanyak 50 orang pekerja. Analisis data menggunakan uji Spearman Rank. Hasil pengujian terhadap hubungan antara umur dengan kelelahan kerja mendapatkan p=0,000 dan r=0,683. Selanjutnya, hasil pengujian terhadap hubungan antara status gizi dengan kelelahan kerja mendapatkan p=0,003 dan r=-0,418. Simpulan penelitian ini ialah terdapat hubungan positif kuat antara umur dengan kelelahan kerja, serta hubungan negatif sedang antara status nutrisi dan kelelahan kerja pada pekerja lapangan di PT Pelabuhan Indonesia IV (Persero) Cabang Bitung.Kata kunci: kelelahan kerja, umur, status gizi, pekerja lapangan